Recreation economics to inform migratory species conservation: Case study of the northern pintail. (15th January 2018) - Mattsson, Brady J.; Dubovsky, James A.; Thogmartin, Wayne E.; Bagstad, Kenneth J.; Goldstein, Joshua H.; Loomis, John B.; Diffendorfer, James E.; Semmens, Darius J.; Wiederholt, Ruscena; López-Hoffman, Laura
Abstract: Quantification of the economic value provided by migratory species can aid in targeting management efforts and funding to locations yielding the greatest benefits to society and species conservation. Here we illustrate a key step in this process by estimating hunting and birding values of the northern pintail ( Anas acuta ) within primary breeding and wintering habitats used during the species' annual migratory cycle in North America. We used published information on user expenditures and net economic values (consumer surplus) for recreational viewing and hunting to determine the economic value of pintail-based recreation in three primary breeding areas and two primary wintering areas. Summed expenditures and consumer surplus for northern pintail viewing were annually valued at $70M, and annual sport hunting totaled $31M (2014 USD). Expenditures for viewing ($42M) were more than twice as high than those for hunting ($18M). Estimates of consumer surplus, defined as the amount consumers are willing to pay above their current expenditures, were $15M greater for viewing ($28M) than for hunting ($13M). We discovered substantial annual consumer surplus ($41M) available for pintail conservation from birders and hunters. We also found spatial differences in economic value among the primary regions used by pintails, with viewing generally valued more in breeding regions than in wintering regions and the reverse being true for hunting. The economic value of pintail-based recreation in the Western wintering region ($26M) exceeded that in any other region by at least a factor of three. Our approach of developing regionally explicit economic values can be extended to other taxonomic groups, and is particularly suitable for migratory game birds because of the availability of large amounts of data. When combined with habitat-linked population models, regionally explicit values could inform development of more effective conservation finance and policy mechanisms to enhance environmental management and societal benefits across the geographically dispersed areas used by migratory species. Highlights: Regional specific values of hunting and viewing a migratory species were calculated. Assessed regions represent core breeding and wintering areas used annually. Economic values totaled over $100M (2014 USD) annually across the core regions. Our analytical approach can be adapted for other bird species in North America. Important step to develop more efficient strategies to conserve migratory species.